The Impact of Technology Acceptance Model and Perceived Risk on Intention to Use E-Filling in the Industrial Revolution 4.0 Era - Laura Angeline; Susan Grace Nainggolan (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study examines whether the Intention to Use E-Filing significantly influenced by one of the Technology Acceptance Model variables, spesifically Perceived Ease of Use and Perceived Risk. The data source is primary data using quantitative data methods. The population in this study were all employees working at PT. Mahato Inti Sawit in total 164 people. The sample consisted of permanent employees with NPWP who worked at PT. Mahato Inti Sawit and used E-Filing totaling 30 respondents using purposive sampling data collection technique. Data analysis and testing consisted of descriptive statistics, classical assumption tests, multiple regression analysis, partial hypothesis testing (T test) and simultaneous (F test), as well as coefficient determination tests. The results of this study show that one of the Technology Acceptance Model variables, spesifically Perceived Ease of Use, has partially significant impact on the Intention to Use E-Filling with calculated T-count of 4.200.> T-table 2.048. Perceived Risk does not affect the Intention to Use E-Filing with calculated T-count of 1.315 > T-table 2.048. Perceived Ease of Use and Perceived Risk simultaneously have a significant effect on the Intention to Use E-FIling with a calculated F-count of 8.819 > F-table 3.35 and a regression coefficient value of 39.5%.